Caractérisation de formations végétales mediterranéennes à partir de données ‘Thematic Mapper’ Une étude de cas en Andalousie (Espagne) (International Journal of Remote Sensing, 1987)
Abstract The study is focused on the characterization of vegetation formations in a Mediterranean area (943 km2) located in southern Spain: herbaceous canopies (rangelands), shrubby vegetation (?matorral?) and complex woody/herbaceous formations (?dehesa?). Vegetation formations (physiognomical units) have been characterized by their spectral responses in the six reflective TM channels and by vegetation indices. From the ratio index TM4/TM3 there has been derived a map displaying seven classes (water, bare soil and five biomass levels reflecting the hierarchy of vegetation formations). Channels TM3, TM4 and TM5 have been considered for a supervised classification into nine land-cover categories (seven vegetation formations, bare soil and water). The proportion of correct classification of vegetation formations is about 78 per cent when considering test areas. Classification made from three principal components gives similar results.
doi: 10.1080/01431168708954777